Evaluación de tres enmiendas orgánicas aplicando dos microorganismos en el cultivo de remolacha (Beta vulgaris) para la recuperación de las propiedades químicas y biológicas del suelo de Salache, Cotopaxi-Ecuador 2022. - Carlosama Paucar, Lesli Yadira (2022)
The purpose of this research work was to evaluate the chemical and biological properties of the soil prior to the incorporation of three organic amendments (Bio Compost, Ferti plus, Humus) applying two microorganisms (Trichoderma spp, Mycorrhizae) at different doses in the cultivation of beet. (Beta Vulgaris) in the bank terraces of the Technical University of Cotopaxi, Salache sector (CEYPSA), an experimental design of Completely Random Blocks (DBCA) was carried out with a factorial arrangement of (3x2x2) +1 with 3 repetitions, giving us a total of 39 experimental units. The results of the investigation were collected every 15 days, which indicates the following variables: the number of plants adapted to Treatment T11 (T11 (Ferti Plus + Mycorrhizae at 20 gr/1 liter) obtained 100% of plants attached. In the height of the T4 treatment (Bio compost + Trichoderma at 20cc/2 liters) with an average of 22.52 in height at 75 days in the number of leaves, T3 (Humus + Trichoderma at 10cc/2 liters) with an average of 10.09 at the weight of the tuber with leaves indicates that the T10 treatment (Bio compost + Mycorrhizae at 20 gr/1 liter) whose average is 2611 kg/ha, its means express that the amendments did act in the beet crop (Beta Vulgaris). However, in the chemical characteristics, the best amendment is Ferti plus, decreasing the Ph (8.95 to 8.68) and increasing the macronutrients N (2.4 to 30.0pmm); P (36 to 241 ppm) K (5.13 meq/100g), organic matter MO (0.50 to 1.54%) in change in the microbiological analysis there was an increase in the mycorrhizae with 75 spores/g and the mycorrhizae a <8 CFU/g. The cost per treatment was T8 (Ferti Plus + Mycorrhizae at 10 gr/1 liter) with $30.13.